TO STUDY THE ULTRA-VIOLET RADIATION MONITORING BY USING THE GAFCHROMIC EBT3 FILMS FOR CLINICAL PURPOSES - Pradeep Goswami; Rakesh Kumar Jain; S. Choudhary; Prabodh Sahay Saxena (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Radiation is to describe the energy that is created and emitted as electromagnetic waves or particles. Electromagnetic radiation includes gamma rays, X-rays, ultraviolet (UV), visible light, infrared light waves, microwaves, and radio waves. Radiation may be classified as either ionizing or non-ionizing depending on its propensity to irradiate materials. The practical barrier between ionizing and non-ionizing radiation is about 13.6 eV, which is the energy required to ionize a hydrogen atom. The electromagnetic spectrum’s ultraviolet (UV) radiation, which has wavelengths between 100 and 400 nanometers, is becoming more widely acknowledged for its dual effects, which include both possible risks and useful uses. It is essential in fields like industrial processing, disinfection, medical treatment (like phototherapy), and environmental monitoring. On the other hand, prolonged or excessive exposure to UV radiation, especially in the UVB (280–315 nm) and UVC (100–280 nm) ranges, may have negative biological consequences, such as immunological suppression, DNA damage, skin cancer, and cataracts. According to material science, UV rays cause structural damage, color fading, and polymer degradation. Radiation dosimetry analysis is used to quantify and track UV exposure accurately because of these wide-ranging impacts.